(untitled) (Marketing Journal, 2025)
The article examines the specifics of commercial real estate valuation in the context of the rapid development of e -commerce. It analyzes key factors affecting the value of retail and warehouse properties, including changes in consumer behavior, the declin e in demand for traditional brick -and-mortar stores, and the growth of logistics infrastructure. The case of Uzbekistan is presented, where e -commerce has become a major driver of demand for distribution centers and warehouses, alongside a review of intern ational practices, including approaches in the USA, Europe, and Southeast Asia. 141 Special attention is given to modern valuation methods utilizing geoanalytics, big data, and machine learning technologies.